Water Accounting Framework in India: Performance Implications and Contextual Factors - Kumar, Praveen (Journal of Environmental Accounting and Management, 2026)
The current investigation analyzed the connection between corporate water disclosures and financial performance in the Indian setting. For this purpose, the water disclosures scores were fetched from the Carbon Disclosure Project reports of all partaking Indian firms for the sample period 2018 to 2019. Further, return on assets, return on capital employed and return on net worth were used as a proxy of sample firms' financial performance. The study revealed that Indian firms have taken initiatives for being corporate water responsible and have openly revealed their endeavours through the Carbon disclosure project. However, this examination did not find any evidence to validate that the water divulgences influence firms' performance. These results are crucial for the managers and investors to know the financial consequences of willful water divulgence by the companies working in developing economies.